Desarrollo de un plan de continuidad de negocio para el área de reaseguros en el proceso de vehículos y sus líneas aliadas de una empresa aseguradora ubicada en la ciudad de Guayaquil para el período 2009 - Huachisaca, J. (2009)
All kind of businesses are vulnerable to the impacts even those big disasters or worries but also for the small interruptions in the day to day activities. Between the principal factors that could affect the business are: technology issues, economic situation of the country where the company make its commerce, natural disasters and others; in which depending on the degree of impact a lot of companies never could recovered. The principal objective that highlights this article is the way to minimize the hazardous consequences produced by the interruption of the dynamic activities of the company through the implementation of a Business Continuity Plan to apply it in a control, appropriate and immediately way. The BCP is a discipline that prepares a company to maintain it business continuity activities, this article is also oriented to the development of the BCP for an Insurance Company in which we analyzes each of the areas involved such as: Reinsurance department, Human Resources, Information and Infrastructure Systems.